Retrospective Assessment of Selenium Status in High Risk Infants. (29th May 2020) - Sherlock, Laura; Vollrath, Kimberly; Ross, Emma; Marshall, Susan; Larez, Nicole; Gorham, Kathryn; Krebs, Nancy
Abstract: Objectives: Selenium (Se) is an essential trace mineral important in neonatal development that contributes to oxidative stress and the inflammatory response. Se deficiency in preterm infants is associated with late onset sepsis, bronchopulmonary dysplasia, poor neurodevelopmental outcomes, and retinopathy of prematurity. Current Se dosing in many US Neonatal Intensive Care Units is based on the amount of Se in term breastmilk. However, it is unclear if this is sufficient and higher levels may be needed to prevent or treat Se deficiency. Our goal was to evaluate if the current practice supplementing total parenteral nutrition (TPN) with sodium selenite 2 mcg/kg/d is sufficient at preventing Se deficiency in high risk infants. Methods: This is a retrospective chart review of Se status at a level IV Children's Hospital NICU from January 1, 2017 to August 30, 2019. Infants were included if born from 22–42 weeks gestation and received TPN for >4 weeks. They were excluded if there was concern for active sepsis or bacterial illness at time of Se draw. Normal Se status was defined as 45–90 ng/mL for infants 0–2 months. Birth weight, IUGR status, gestational age, and % enteral feeds were evaluated. Se deficient infants received higher Se dosing at 5–7 mcg/kg/d. Repeat levels were evaluated after 4 weeks. Results are reported as mean ± SD. Results: Se status was assessed for 39 infants. Average gestational age was 29.8 ± 5.36 weeks. Average birth weight was 1499 ± 837 g. At the time of first Se assessment, 78% of infants were Se deficient, with a mean Se level of 40.95 ± 12 ng/mL. Repeat Se levels on higher dosing was assessed in 23 infants. After >4 weeks of higher Se dosing, 35% of infants remained Se deficient, with a mean Se level of 54.04 ± 14 ng/mL. By t-test, statistically fewer infants were Se deficient on higher Se dosing ( P < 0.0003). Conclusions: Infants on prolonged TPN >4 weeks are at high risk for Se deficiency. Se dosing at 2 mcg/kg/day is insufficient in preventing deficiency for a majority of these babies. Higher Se dosing improved the percentage of Se sufficient infants, but a third remained deficient. Future studies are needed to prospectively determine if higher Se in TPN prevents Se deficiency. Funding Sources: University of Colorado, Section of Neonatal-Perinatal Medicine.